Association between blood pressure components and the presence of carotid plaque among adults aged 45 years and older: a population-based cross-sectional study in rural China. Issue 5 (October 2019) - Dong, Shaozhuang; Gao, Jie; Wang, Conglin; Liu, Jie; Gu, Hongfei; Tu, Jun; Wang, Jinghua; Zhang, Wenjuan; Ning, Xianjia
Abstract : Objective: Pulse pressure is strongly associated with the early development of large-vessel atherosclerotic disease. However, the relationship between pulse pressure and carotid plaque in China is unknown. Thus, we investigated the associations of pulse pressure and mean arterial pressure with the presence of carotid plaques in a low-income population in rural China. Participants and methods: Residents, aged ≥45 years, without histories of stroke or cardiovascular disease were enrolled. Participant demographics, previous medical histories, and lifestyle information were collected; anthropometric measures, serum profiles, and B-mode ultrasonographic investigations were also performed. Results: The mean age of participants (n = 3789) was 59.9 years overall (men 61.1 years; women, 59.1 years). The mean SBP (146.42 mmHg) and DBP (86.81 mmHg), pulse pressures (59.61 mmHg), and mean arterial pressures (106.68 mmHg) were high in this population. The odds ratio (95% confidence interval) for the association of pulse pressure with the presence of carotid plaques was 1.028 (1.023–1.033), in the univariate analysis. After gradual adjustment for demographic features, risk factors, and serum profile measurements, this positive association remained statistically significant (all, P < 0.001). However, there was no significant relationship between mean arterial pressure and the presence of carotid plaques. Conclusion: These findings suggest that an elevated pulse pressure is an independent risk factor for the presence of carotid plaque. These results suggest that enhanced monitoring of blood pressure components, among low-income residents, is crucial for decreasing the risk of stroke and other cardiovascular disease in China.